Dimensions of the psychological emptiness and its relation with suicide history among college students - Xing Hang; Wenqi Lü; Yan Wu; Yan Wu; Xudong Kang; Ye Zhu (Frontiers in Psychology, 2025)
BackgroundThe psychological emptiness (PE) presents a state of emotional emptiness and lack of meaning, and is increasingly relevant in modern society. However, few studies have tried to assess its dimension and suicide history. This study aims to establish the factorial structure of PE and compare its predictive power against a standard depression inventory.MethodsA total of 45,335 university students participated in the study. The 20 items involving lack of purpose, depression, and meaninglessness in life were used to evaluate the PE, alongside the Beck Depression Inventory (BDI). Exploratory factor analysis (EFA) was employed to identify the structure of the 20 items, while confirmatory factor analysis (CFA) was employed to confirm the construct validity of the model. Logistic regression analysis was conducted to assess the predictive relationship between the identified factors and suicide history.ResultsEFA identified a three-factor structure: Depression and Self-Harm/Suicidal Tendencies (DST), Life Meaning and Purpose (LMP), and Study Motivation (SM). The three factors accounted for 23.1, 12.6, and 11.9% of the total variance, respectively. CFA confirmed the construct validity of the model, which showed acceptable fit indices and high internal consistency (Cronbach’s α > 0.80). Logistic regression analysis revealed that DST was the strongest predictor of suicide risk (AUC = 0.84), outperforming traditional depression scales (BDI, AUC = 0.58).ConclusionThe present study provides a comprehensive framework for understanding PE. The PE may include three psychological dimensions, while DST is a strong predictor of suicide history.